A HAND IN HAND WITH TIMOR EXCHANGE : PROJECT BETWEEN VIANA DO CASTELO POLYTECHNIC AND THE PORTUGUESE SCHOOL OF DILI – CELP – RUY CINATTI - Anabela, Anabela Moura; Pestana, Assunção (Advances in Social Sciences Research Journal, 2021)
Hand in hand with Timor (De mãos dadas com Timor) is a project that explores cultural competencies, social interaction through the Arts and Communication which has promoted cognitive development and a systematic contact between participants from very diverse cultural contexts (Portuguese students in two classes of the 1st year Basic Education Teacher Training BA Degree at the Higher School of Education of Viana do Castelo Polytechnic [ESEVC-IPVC], attending the subject entitled Theories and Practices of Visual and Performing Arts, and Timor children, teachers and educators working in the Pre-School level of Education at the Portuguese School of Dili - CELP - Ruy Cinatti, Timor). This international exchange arose from contacts made between the teacher of Visual Arts at ESEVC-IPVC and Flor Gomes, former student of ESEVC-IPVC, with a BA degree in Visual and Technological Education and a Master in Art Education at ESEVC-IPVC, teacher in statutory mobility, currently working in Timor between 2020 and 2022. This article, written by two researchers from the Art Education area, addresses a Portuguese project which emphasised an action-research underpinned in an interdisciplinary approach, using comics as teaching strategy in developing cultural competencies of eighty Portuguese students (nº=80) of a Basic Education Course. The findings of such collaboration using video as the communication support for this international exchange, show the positive effects of such Project that promoted the overall cultural and artistic competencies of students involved, either in Portugal or in Timor. It is concluded that such curricular experiment had on students, on their motivation and awareness of how illustration and video can work together with popular literature, staging and illustrating it. It also highlights how imagination, creativity, dialogue and cultural competencies of children can promote a deeply collaborative work at local, regional, national and international levels, despite the fact that we are living in a period of pandemic and confinement.